TO WORK ABILITY SUPPORT SYSTEM OF “BELARUS”-TRACTOR OPERATOR - T. Mikulick; G. Reyzina (Наука и техника)
The paper considers problems pertaining to operational diagnosis of transport facility operator (driver), describes a basis algorithm of physiological operator’s characteristics with the purpose to control his activity during non-standard situations. Such approach is presented as one of the possible ways to improve operational efficiency of agricultural machinery during production and operations.